Fathering the Nation. From Mustafa Kemal to Atatürk - Türköz, Meltem (Traditiones, 2017)
<span style="line-height: 115%; font-family: ’Helvetica’,’sans-serif’; font-size: 11pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: AGaramondPro-Italic; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">This article provides an overview of the critical scholarship on the emergence and various stages of the veneration of Turkey’s founder Mustafa Kemal Atatürk over the decades, demonstrating how specific political environments have played a role. <span style="line-height: 115%; font-family: ’Helvetica’,’sans-serif’; font-size: 11pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: AGaramondPro-Italic; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">*** <span style="line-height: 115%; font-family: ’Helvetica’,’sans-serif’; font-size: 11pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: AGaramondPro-Italic; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">Razprava podaja kritičen pregled nastanka in različnih stopenj čaščenja ustanovitelja Turčije Mustafa Kemala Atatürka v preteklih desetletjih. Pri čemer avtorica pokaže, kako vlogo so imela posebne politične okoliščine.